Effects of frequency of feeding on Nile tilapia (Oreochromis niloticus) growth in a closed system - Al-Hamadany, Qusay (Iraqi Journal of Aquaculture, 2025)
This study aims to assess the influence of feeding frequency on growth, feed conversion efficiency, and survival rate of Nile tilapia (Oreochromis niloticus). The experiment involved 80 fish of comparable size, and the average weight was 5.78 g. Each of the eight 45-liter tanks contained ten fish. The experiment includes two replicates for each feed frequency. The fish were categorized into four categories based on their feeding frequency: once daily (A), twice daily (B), thrice daily (C), and four times daily (D). The fish were fed at a daily rate of 3% of their body weight. The highest weight gain 12.52 g, relative growth rate 214.57%, specific growth rate 2.605 g/day%, and feed conversion rate 2.06 were observed in Treatment C, which was provided three times daily. Moreover, all these values varied significantly from the other treatments, and the analysis of variance indicated substantial differences (p < 0.05). According to the results of the present study, Nile tilapia growth in aquaculture systems is facilitated by an increase in feeding frequency; this study indicates that feeding fish thrice daily may enhance their growth and feed conversion efficiency; hence, farmers should use this practice. The study revealed that feeding frequency is essential for enhancing production in aquaculture, as regulating feeding intervals can result in improved growth rates of Nile tilapia.